2014
DOI: 10.1146/annurev-med-061512-105739
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer

Abstract: Thyroid cancer is rapidly increasing in incidence, but the mortality rate remains flat. Debate has arisen over the need to detect or treat most thyroid cancers early, given their favorable natural history. The appropriate extent of surgery for thyroid cancer is also controversial: some researchers advocate partial and others total thyroidectomy; some advocate prophylactic central cervical lymph node dissection, whereas others only rarely recommend lymphadenectomy. Although radioactive iodine is effective, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
212
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(240 citation statements)
references
References 48 publications
1
212
0
3
Order By: Relevance
“…Risk factors for TC include being female, having a history of goiter or thyroid nodule, a family history of TC, low-iodine diet, radiation exposure and obesity. 5 …”
Section: Thyroid Cancer (Tc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for TC include being female, having a history of goiter or thyroid nodule, a family history of TC, low-iodine diet, radiation exposure and obesity. 5 …”
Section: Thyroid Cancer (Tc)mentioning
confidence: 99%
“…ATC accounts for 2-5% of TCs and is one of the most aggressive and lethal human malignancies. 5 PTC is associated with mutations in genes that encode for effectors involved in the mitogen-activated protein kinase (MAPK) and the PI3K-AKT pathway, including RET (encoding proto-oncogene tyrosine-protein kinase receptor ret), RAS genes (which encode small GTPases) and BRAF (encoding serine/threonine kinase B-raf). 6 A comprehensive multiplatform analysis of 496 PTCs found that the most common genetic alterations were found in BRAF and RAS, suggesting their pivotal role in driving the PTC initiation.…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…The first type comprises follicular cells that surround the colloid follicles and uptake iodine to synthesize thyroid hormones; anaplastic thyroid and well-differentiated tumors such as papillary and follicular can develop in these cells. The second type comprises parafollicular cells whose main function is to secrete calcitonin; parafollicular cells have attracted interest primarily as the origin of medullary thyroid cancer (MTC) [1]. Thyroid cancer (TC) is the 9th most common malignancy and the most common endocrine cancer [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer is the most common type of malignancy in endocrine, which stems from parafollicular or follicular thyroid cells 1. Several histologic types of thyroid cancer have been identified, including follicular thyroid carcinoma, papillary thyroid carcinoma, and anaplastic thyroid carcinoma 2.…”
Section: Introductionmentioning
confidence: 99%